Ritual obrezovanja - obrezovanje rituala - Mertik, Tina (Etnolog. Nova vrsta (Ljubljana), 2014)
In central Java and Indonesia circumcision of girls is generally considered a common, obligatory tradition. It is most usually performed on girls when they are around 35 days old, and together with cutting their hair and perforating their ears. Little is known about the practice itself, while the available literature and field data refer to "scraping" the clitoris with a razor and curcuma, said to be performed without actual cuts or bleeding. The circumcision of genitalia is referred to in Indonesia with the term tetesan, literally meaning "drop". The reasons for female genital mutilation and its justification vary. It is known that the traditional practice of circumcising girls was performed to reduce their sexual lust and thus maintain their virginity and sexual abstinence. But there are also other reasons, for instance religious ones (in the name of Islam), social ones (control), and aesthetic ones. In spite of the legal ban issued by the Indonesian government in 2006, FGM is still very common in Indonesia and in recent times it has even become medicalised. Some towns (and villages) go as far as organizing "competitions" in circumcision - who performs it quicker and better. It must be said though that people are increasingly aware that the practice is banned, but the road to liberation remains long and hard.
Keywords: ethnology; etnologija; ljudski običaji; iniciacija; deklice; obrezovanje; Indonezija